ICT and Learning Attitude towards Students’ Academic Paragraph Writing in College Level - Hayati, Rita; Anggraini, Hesti Wahyuni; Jaya, Hariswan Putra (ENGLISH FRANCA : Academic Journal of English Language and Education, 2021)
The use of technology has been growing rapidly in recent years. The technology applies to support the success of language learning, for example, providing web-based learning, mobile-based learning, educational videos, stimulation, online learning platforms, and many more.  Learning attitude also determines to achieve the language learning goals. Then, the complexity of English writing causes the students’ denial to take English writing classes. This study aimed at finding out whether there was a significant correlation among ICT writing. Seventy-one students of the English Education Study Program got involved in this correlational study. The data were gained from primary and secondary sources; those are a 15-item ICT use questionnaire, a 20-item learning attitude questionnaire, and documentation of students’ writing. The findings reported that there was a significant correlation among the three variables statistically since the significant value was 0.006 (< 0.05). The value of adjusted r2 was 0.114 which means ICT use and learning attitude contributed 11.4 % to the students’ English academic paragraph writing.Key words: ICT, learning attitude, academic paragraph writing